The Learning Management Through theStudent Team Achievement DivisionCombined withMind Mapping Techniques to Develop Learning Achievement For 1st Year of Secondary Vocational Students - Lingzhu, Xiao; Jermtaisong, Rossarin; Lhongsap, Pornpirom (Journal of Roi Kaensarn Academi, 2023)
The objectives of this research were to: 1) compare the pre-and post-learning achievement of 1st-year secondary vocational studentsstudying through the traditional approach, 2) compare the pre-and post-learning achievement of the students studying through the Student Team Achievement Division combined with Mind Mapping techniques, and 3) compare the postlearning achievement of students studying through the traditional approach and the learning management through the Student Team Achievement Division combined with Mind Mapping techniques. The research sample was 40, selected by cluster random sampling, 1st year of tourism major students at the secondary vocational school, Beijing, China in the academic year 2022. The research instruments consisted of 1) a learning management plan based on the traditional approach, 2) a learning management plan based on Student Team Achievement Division combined with Mind Mapping techniques, and 3) a learning achievement test. The statistics used for data analysis were mean, standard deviations, independent samples t-test, and dependent samples t-test.The research results showed that: 1) the post-learning achievement of 1st-year secondary vocational studentsstudying through the traditional approach was higher than the pre-learning at a statistical significance level of .05., 2) the post-learning achievement of students studying throughthe Student Team Achievement Division combined with Mind Mapping techniques was higher than the pre-learning at a statistical significance level of .05., and 3) the students learning achievement of those studying throughthe Student Team Achievement Division combined with Mind Mapping techniques was higher than those studying through the traditional approach at a statistical significance level of .05.